2016
DOI: 10.1038/srep39151
|View full text |Cite
|
Sign up to set email alerts
|

Exercising alone versus with others and associations with subjective health status in older Japanese: The JAGES Cohort Study

Abstract: Although exercising with others may have extra health benefits compared to exercising alone, few studies have examined the differences. We sought to examine whether the association of regular exercise to subjective health status differs according to whether people exercise alone and/or with others, adjusting for frequency of exercise. The study was based on the Japan Gerontological Evaluation Study (JAGES) Cohort Study data. Participants were 21,684 subjects aged 65 or older. Multivariable logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…It should be noted that there was a very high ratio of individuals who were living with others and of individuals receiving emotional support (about 90% for each). Similar ratios were found in other large-scale studies that we conducted on older Japanese adults 23 , 39 . This indicates that the population in the present study does not differ greatly from the trends for older adults without functional disabilities in Japan as a whole.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It should be noted that there was a very high ratio of individuals who were living with others and of individuals receiving emotional support (about 90% for each). Similar ratios were found in other large-scale studies that we conducted on older Japanese adults 23 , 39 . This indicates that the population in the present study does not differ greatly from the trends for older adults without functional disabilities in Japan as a whole.…”
Section: Discussionsupporting
confidence: 90%
“…The odds ratio for Ewo (2+/wk) was 0.40 (0.24–0.68), but it was 0.74 (0.43–1.26) for Ea-only (2+/wk), showing a weaker relationship. Previous studies indicated that, compared with only exercising alone, exercising with others lowers the prevalence of poor self-rated health 23 and the risk of poor mental health 35 , difficulties in activities of daily living 36 , and functional disability 33 . The results of the present study indicate that exercising with others may have a similar effect on depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations